2021
DOI: 10.1021/acs.analchem.0c05266
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the Selectivity Dilemma of Benzopyrylium–Coumarin Dyes in Fluorescence Sensing of HClO and SO2

Abstract: Benzopyrylium–coumarin fluorescent probes for sensing hypochlorous acid (HClO) or sulfur dioxide (SO2) are unable to distinguish between HClO and SO2 because the two compounds can react with the 4-position of benzopyrylium–coumarin dyes through the nucleophilic attack. In the current work, we introduced a phenoxazine moiety to the benzopyrylium–coumarin dye to synthesize a new fluorescent probe PBC1, which can dually sense HClO and SO2 and generate distinct fluorescence signals with rapid response time and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…After adding HSO 3 À , the emission intensity of 18-OH, the product of probe 18 and Cys, decreased at 640 nm and increased at 540 nm within 90 s. Images of zebrafish incubated with probe 18 and The benzopyrylium group of flavylium dyes could serve both as the recognition site for SO 2 and HOCl, leading to poor selectivity. To solve this problem, Han et al 78 reported a dualfunctional fluorescent probe (19) for tracking HClO and SO 2 in vitro and in vivo. Probe 19 consisted of a phenothiazine moiety as the recognition site for HClO and a benzopyrylium moiety as the recognition site both for HClO and SO 2 (Fig.…”
Section: Fluorescent Probes For Reactive Sulfur Speciesmentioning
confidence: 99%
“…After adding HSO 3 À , the emission intensity of 18-OH, the product of probe 18 and Cys, decreased at 640 nm and increased at 540 nm within 90 s. Images of zebrafish incubated with probe 18 and The benzopyrylium group of flavylium dyes could serve both as the recognition site for SO 2 and HOCl, leading to poor selectivity. To solve this problem, Han et al 78 reported a dualfunctional fluorescent probe (19) for tracking HClO and SO 2 in vitro and in vivo. Probe 19 consisted of a phenothiazine moiety as the recognition site for HClO and a benzopyrylium moiety as the recognition site both for HClO and SO 2 (Fig.…”
Section: Fluorescent Probes For Reactive Sulfur Speciesmentioning
confidence: 99%
“…Therefore, it is urgent to improve the temporal and spatial resolution of probe imaging and reduce interference. Other challenges in developing probes for HClO detection include designing probes that respond quickly and selectively to HClO and other ROS, and that perform good imaging in living systems. Currently reported probes use thioether as the recognition group; however, this similar structure has been pointed out to respond to other ROS, lacking specificity , Therefore, a high-quality fluorescent probe with excellent selectivity to HClO should be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, fluorescent probes are widely used in the study of various life phenomena in cells [ 20 , 21 , 22 ] and in vivo due to their advantages of low damage, high specificity, high sensitivity and real-time dynamic imaging [ 23 ]. In previous studies, benzopyranium has been proven to be an efficient structure to detect sulfur dioxide [ 24 , 25 ], and its recyclable and reversible detection with some oxidizing species may yet be realized [ 26 , 27 , 28 ]. In this paper, we designed and synthesized a fluorescent B2P probe with benzopyranium as the detection site, which can reversibly detect SO 2 and FA.…”
Section: Introductionmentioning
confidence: 99%